Proceedings of the ACM Annual Conference on - ACM '72 1972
DOI: 10.1145/800194.805904
|View full text |Cite
|
Sign up to set email alerts
|

A relational data base management system

Abstract: In this paper the design criteria and the overall organization of MORIS, a new general purpose data management system, are illustrated.The system is based on a relational model of data, in which the data base is view ed as a collection of time varying relations of assorted degrees. The capabilities offer ed by this model are discussed. The archi--tecture of the system is illustrated,which is designed to provide independence of application programs from growths in data types and changes in data representation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Among many relational query languages proposed [BI,B2,B3,C3,GI,SI], SEQUEL is an English-like query language with outstanding features.…”
Section: The Query Language -Raquelmentioning
confidence: 99%
“…Among many relational query languages proposed [BI,B2,B3,C3,GI,SI], SEQUEL is an English-like query language with outstanding features.…”
Section: The Query Language -Raquelmentioning
confidence: 99%
“…For example, although information on education and child exist in the same row in the table, there does not exist any relationship between them except that they are both related to the same person. Hence these tables or Forms are not relational tables [17 -2 I], but perhaps somewhat akin to Bracchi's unnormalized relations [22][23][24]. Note that additional visual aids can be included in the Form's layout if so desired by the user, e.g.…”
Section: Conceptual Data Representationmentioning
confidence: 99%
“…Several existing languages [7,19,22,25,26] were investigated to determine if they may be used for data translation. It was found that they are either too low level, lack the required capability, or are too mathematically oriented for the type of users we visualized.…”
Section: Altering Values Of Data Instances In Different Mannersmentioning
confidence: 99%
“…Bracchi et al [14] in designing a language (COLARD) for a relational database management system, decided to allow the definition of nonnormalized relations. However, because COLARD is based on first-order predicate calculus, one needs mathematical sophistication to use the language, in spite of the English flavor injected into it.…”
Section: Design Criteria and Underlying Conceptsmentioning
confidence: 99%